Implementation of a LQG controller for a structural model´s seismic protection with oe degree of slackness (2017)
It presents the modeling and the identification of a one grade looseness structure, and also an active LQG comptroller's design, which is intended to reduce the structural vibrations of a floor, facing some seismic vibrations in its base. The controller uses as the source the first level strucutre´s acceleration and its design is based upon the model and the structural system's identification, the one which was carried out. The model was verified by a simulation and experimentation, by exciting the structure at its base with the seismic waves provided by el centro and Armenia, and observing the realtive structure's acceleration decreases, which were up to 63.68% and the relative displacements lower than 1% in height.